School Counselors and the Multidisciplinary Team Process A Consultant Role - Schrank, Frederick A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
A Wisconsin law has been enacted to ensure adequate educational programming for children with exceptional educational needs. Multidisciplinary teams (M-Team) are mandated to carry out the requirements of this legislation. One function of the M-Team is that of parental consultation. According to the law, parents must be notified that their children are to be referred to such a team. In addition, members of the team must confer with parents after they have met for assessment and programming. This article reviews the preparation of school counselors, their orientation toward child growth and development, and their expertise in facilitating communication. It is suggested that school counselors can be effective parental consultants for the M-Team. (Author)
Guidelines for Pupil Services, v14 n2 p60-62 Win 1975-76.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Consultants; Counselor Role; Counselor Training; Exceptional Child Services; Guidance Objectives; Interdisciplinary Approach; Parent Conferences; Program Descriptions; State Legislation; Teamwork; Wisconsin; Reports, Descriptive